Tobacco cessation effects on oral health by group and individualized motivational therapy in 12 to 18 years old boys - A randomized controlled study - Kinjal Patel; Anshula Deshpande; Aishwarya Jain; Yash Shah; Pulkit Kalyan (Wolters Kluwer Medknow Publications, 2020)
Background/Introduction: Adolescents are the most vulnerable population to initiate tobacco use. It is now well established that most of the adult users of tobacco start tobacco use in their childhood or adolescence. Aim: The purpose of this study is to compare and evaluate the Group Motivational Therapy (GMT) and Individualised Motivational therapy (IMT) for tobacco cessation in adolescents. Methodology: Oral screening was done in a village named Vehra Khadi near Anand. One hundred and eight adolescents aged between 12 and 18 years were included in the study. They were randomly divided into three groups namely Group 1 - Interventional group consisting of 36 adolescents who were given GMT; Group 2 - Interventional group consisting of 36 adolescents who were given IMT; and Group 3 -3 6 age - matched Negative control group. Hence, a total sample size of 108 was evaluated for tobacco consumption frequency, passive smoking, gingival index, and stain index and followed up for 9 months for the effect of both interventional group as well as positive control. Results: Frequency of tobacco consumption was reduced from baseline to 9 months' follow-up for both the interventional groups, which was statistically significant with <0.001 percent P value showing 84.38% change by intervention 1 and 98.30% in intervention 2. Conclusion: Group and individualized motivation serves as an effective means for tobacco cessation among adolescents. Improvement in gingival health and reduction of the tobacco consumption was observed with motivational intervention.